Acromegaly and cardiovascular outcomes: a cohort study. (4th December 2021) - Hong, Sangmo; Kim, Kyung-Soo; Han, Kyungdo; Park, Cheol-Young
Abstract: Aims: Cardiovascular disease is a common complication in acromegaly. We investigated the risk of cardiovascular disease and mortality in patients with acromegaly in a large-scale population using nationwide data in Korea. Methods and results: We performed a nationwide, retrospective, observational, cohort study of patients with acromegaly ( n = 1874) and age- and sex-matched subjects without acromegaly ( n = 9370) for a mean follow-up of 7.5 ± 3.2 years. The study outcomes were myocardial infarction, stroke, atrial fibrillation, congestive heart failure, and all-cause death. All outcomes were analysed by Cox proportional hazards regression analysis while controlling for age, sex, household income, place, Type 2 diabetes, hypertension, and dyslipidaemia. The incidence (per 1000 person-years) of atrial fibrillation (3.06 vs. 1.70; P = 0.001), congestive heart failure (3.11 vs. 1.63; P < 0.001), and all-cause mortality (6.31 vs. 4.03; P < 0.001) in patients with acromegaly was higher than in controls. However, the incidence of myocardial infarction and stroke did not differ between groups. After adjustment for covariates, the risk for atrial fibrillation [hazard ratio (HR): 1.59; 95% confidence interval (CI): 1.09–2.31], congestive heart failure (HR: 1.54; 95% CI: 1.06–2.25), and all-cause mortality (HR: 1.31; 95% CI: 1.01–1.69) was significantly higher in patients with acromegaly. In time lag sensitivity analysis, a higher risk for atrial fibrillation was observed only in the first 4 years after diagnosis in acromegaly patients compared with controls (HR: 3.05; 95% CI: 1.94–4.79). Conclusion: Patients with acromegaly were at higher risk for atrial fibrillation, congestive heart failure, and all-cause death. The risk of atrial fibrillation had a time-dependent association with acromegaly. Graphical Abstract: